2022
DOI: 10.1002/smll.202107574
|View full text |Cite
|
Sign up to set email alerts
|

Boron‐Based Multi‐Resonance TADF Emitter with Suppressed Intermolecular Interaction and Isomer Formation for Efficient Pure Blue OLEDs

Abstract: Multi‐resonance (MR) thermally activated delayed fluorescent (TADF) emitters are highly attractive due to their superior color purity as well as efficient light‐harvesting ability from singlets and triplets. However, boron and nitrogen‐based MR‐TADF emitters suffer from their strong π–π interaction owing to their rigid flat cores. Herein, a boron‐based multi‐resonance blue TADF emitter with suppressed intermolecular interaction and isomer formation is developed through a simple synthetic process by introducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 85 publications
1
23
0
Order By: Relevance
“…Furthermore, we investigated the theoretically achievable EQE values of the devices using optical simulations. The horizontal dipole ratios (HDRs) of the emitters were precisely checked using thin films comprising mCBP:5 wt % doped emitters (Figure e). , The emitters exhibited similar D–A configurations such that they had similar HDR values of 72 ± 2% for D1 , and 70 ± 2% for D2 and D3 , respectively. Using the PLQYs and HDRs of the emitters and TADF-OLED structures, we performed optical simulations, and the results are shown in Figure f as a contour map.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we investigated the theoretically achievable EQE values of the devices using optical simulations. The horizontal dipole ratios (HDRs) of the emitters were precisely checked using thin films comprising mCBP:5 wt % doped emitters (Figure e). , The emitters exhibited similar D–A configurations such that they had similar HDR values of 72 ± 2% for D1 , and 70 ± 2% for D2 and D3 , respectively. Using the PLQYs and HDRs of the emitters and TADF-OLED structures, we performed optical simulations, and the results are shown in Figure f as a contour map.…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al reported a new pure blue emitter named mBP‐DABNA‐Me , wherein xylene and meta‐phenyl groups were introduced into the DABNA core to effectively suppress aggregation‐caused quenching and prevent the isomer formation in the reaction. [ 100 ] The mBP‐DABNA‐Me manifested pure blue emission with λ PL of 464 nm and FWHM of 28 nm in the toluene solution. Notably, the doped film exhibited only a 3 nm redshift compared to the solution attributed to the suppressed π–π interactions, and as a result, the PLQY yielded in 97%.…”
Section: Blue/deep‐blue Mr‐tadf Emittersmentioning
confidence: 99%
“…In order to achieve high-color purity deep-blue emission, narrowband chromophores with electroluminescent (EL) emission peaks at 460 ± 5 nm are required. At the same emission peak, the narrower FWHM manifests a smaller CIE y value (and a higher current efficiency/CIE y index) and relatively lower excited state (S 1 ) energies due to the bathochromic shift for the spectral onset. However, owing to the difficulty in managing large bandgap chromophores and maintaining efficient radiative emissions, molecular design strategies for color-saturated deep-blue and high photoluminescence quantum yield (PLQY) emitters are still rare and challenging. …”
Section: Introductionmentioning
confidence: 99%